PENERAPAN QUICK ON THE DRAW DALAM PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR EKONOMI SISWA KELAS XII IPS 2 SMA NEGERI 2 PEKANBARU: Application Of Quick On The Draw In Learning Cooperative Learning Outcomes For Improving Economy Class XII IPS 2 SMA Negeri 2 Pekanbaru - Tini, Ratna (Perspektif Pendidikan dan Keguruan, 2017)
This research is a classroom action research that aims to improve the learning process and improve learning outcomes of economics students with the application of Quick On The Draw in cooperative learning. The subjects were students of class XII IPS 2 SMA Negeri 2 Pekanbaru in the first semester of the academic year 2013/2014, totaling 40 people, consisting of 19 male students and 21 female students with academic ability levels are heterogeneous. The study consisted of two cycles, each cycle consisting of four phases: planning, implementation, observation and reflection. Each end of the cycle carried out daily tests. The data collection is done by observation techniques and techniques written test. Data was analyzed using descriptive qualitative analysis techniques of narrative and descriptive statistical analysis. Results of research on the observation sheet shows the activity of teachers and students have done well after taking action even though there are still some deficiencies. Teacher activity in accordance with the planning and activities of students also increased to be active both in discussions and when answering a question card set. Criteria for success of the action on this study is the result of increased student learning that can be seen from the increasing value of students can be seen from the analysis of the achievement of KKM. If the number of students who reach KKM on daily tests 1 and 2 daily test more than the basic score, it can be said Shiva value increases. The number of students who reach KKM on a base score, daily test I (first cycle), daily test II (second cycle) respectively are 30%, 50% and 75%. The results of this study indicate that the application of Quick On The Draw in cooperative learning can improve student learning outcomes economy class XII IPS 2 SMA Negeri 2 Pekanbaru semester of academic year 2013/2014.